Prevalence and reporting of recruitment, randomisation and treatment errors in clinical trials: a systematic review - Yelland, LN; Kahan, BC; Dent, E; Lee, KJ; Voysey, M; Forbes, AB; Cook, JA (SAGE Publications, 2018)
Background/Aims: In clinical trials, it is not unusual for errors to occur during the process of recruiting, randomising and providing treatment to participants. For example, an ineligible participant may inadvertently be randomised, a participant may be randomised in the incorrect stratum, a participant may be randomised multiple times when only a single randomisation is permitted or the incorrect treatment may inadvertently be issued to a participant at randomisation. Such errors have the potential to introduce bias into treatment effect estimates and affect the validity of the trial, yet there is little motivation for researchers to report these errors and it is unclear how often they occur. The aim of this study is to assess the prevalence of recruitment, randomisation and treatment errors and review current approaches for reporting these errors in trials published in leading medical journals. Methods:We conducted a systematic review of individually randomised, phase III, randomised controlled trials published in New England Journal of Medicine, Lancet, Journal of the American Medical Association, Annals of Internal Medicine and British Medical Journal from January to March 2015. The number and type of recruitment, randomisation and treatment errors that were reported and how they were handled were recorded. The corresponding authors were contacted for a random sample of trials included in the review and asked to provide details on unreported errors that occurred during their trial. Results: We identified 241 potentially eligible articles, of which 82 met the inclusion criteria and were included in the review. These trials involved a median of 24 centres and 650 participants, and 87% involved two treatment arms. Recruitment, randomisation or treatment errors were reported in 32 in 82 trials (39%) that had a median of eight errors. The most commonly reported error was ineligible participants inadvertently being randomised. No mention of recruitment, randomisation or treatment errors was found in the remaining 50 of 82 trials (61%). Based on responses from 9 of the 15 corresponding authors who were contacted regarding recruitment, randomisation and treatment errors, between 1% and 100% of the errors that occurred in their trials were reported in the trial publications. Conclusions: Recruitment, randomisation and treatment errors are common in individually randomised, phase III trials published in leading medical journals, but reporting practices are inadequate and reporting standards are needed. We recommend researchers report all such errors that occurred during the trial and describe how they were handled in trial publications to improve transparency in reporting of clinical trials.